Menganalisis dan Merancang Ulang User Interface Sistem Informasi Perpustakaan dengan Metode User-Centered Design - Turnip, Togu Novriansyah; Lumban Gaol, Tiurma; Tesalonika, Risdo Marisi; Tampubolon, Beny Luis; Yuliana, Inez Cecilia Tiurma (Universitas Harapan Medan, 2024)
The Library Information System has an unattractive interface. This is evidenced by the distribution of satisfaction questionnaires to a number of people from the IT Del community, including students, lecturers, and staff who think that the PI Del Library Information System user interface (SIPP) is less attractive so that users experience difficulties in carrying out activities in the system such as finding books that are wanted. SIPP User Interface redesign aims to improve the appearance of the user interface on the system. The purpose of this study was to redesign the user interface of the library information system, in accordance with User Centered Design (UCD) and improve the usability component of the standard user interface. s In this study the User-Centered Design (UCD) methodology was used in the process of redesigning the user interface. SIPP. In the UCD methodology, 3 iterations were carried out. Each iteration is carried out with 4 research stages. In the process of planning the human centered process, the user context is determined, in the specify the context of use stage, user needs are determined using personas, in the specify user and organizational requirements stage, an evaluation is carried out for users regarding the current system, in the produce design solution stage, it is carried out temporary design from the results of user-centered system evaluation, and the evaluate designs against user requirements stage is re-evaluated by users against the results of the temporary design in the form of wireframes and submitted a questionnaire as a form of assessment to compare each iteration. The new design is in the form of improving the page appearance of the PI Del Library Information System with a User Centered Design process. The UCD process is carried out with 3 iterations